PASTEURIZED MEAT PRODUCTS II. BACTERIOLOGICAL PROPERTIES - ΣΚΑΡΒΕΛΗΣ, Α. (Journal of the Hellenic Veterinary Medical Society, 1972)
The author makes a review of the bacteriological properties of pasteurized meat products and especially of ham. He refers to the different factors responsible for the endogenous as well the exogenous contamination of these products.